PENGARUH JUMLAH BENIH PER LUBANG DAN JARAK TANAM SORGHUM MANIS (Sorghum bicolor (L.) Moench) TERHADAP PERFORMA VEGETATATIF PADA RATUN KETIGA - Annisa Nurhaliza; Liman Liman; Agung Kusuma Wijaya; Muhtarudin Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This research aimed to know the effect of number of seeds per hole and plant spacing on the vegetatitive performance of forage sorghum. This research was conducted on July--September 2019 at Integrated Field Laboratory and Animal Nutrition and Feed Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The study was done based on Factorial Randomized Block Design. The first treatment consisted of 3 number of seeds which was one, two, and three seeds and grouped by different land contours. The second treatment consisted of plant spacing which was 50 x 30 cm, 66,6 x 30 cm and 100 x 30 cm. The data obtained were analyzed using variance analysis and continued by using Duncan Multiple Range Test at 5% level of significance. The results showed that there was no interaction (P>0,05) between the number of seeds per hole and plant spacing on fresh matter production, number of tillers, proportion of leaves stems, plant height, and number of leaves of sorghum forage at the third ratoon. The number of seeds per hole significantly affected (P<0.05) on plant height, but did not significantly affect the fresh matter production, number of tillers, proportion of leaf stems, plant height, and number of leaves sorghum forage. The result also showed that plant spacing did not significantly affected (P>0,05) on fresh matter production, number of tillers, proportion of leaf stems, and number of leaves of sorghum forage at the third ratoon. Keywords: number of seeds per hole, plant spacing, Sweet sorghum, third ratoon, vegetative performance